Synoeca ilheensis sp. nov., a new social wasp (Hymenoptera, Vespidae, Polistinae) from Brazilian lowland Atlantic Forest - Lopes, Rogério B.; Menezes, Rodolpho S. T. (Zootaxa, 2017)
Synoeca de Saussure, 1852 is a small genus belonging to the Neotropical swarm-founding wasp tribe Epiponini Lucas, 1867. The nests of these insects can become large, with combs directly attached to the substrate and with an envelope resembling the back of an armadillo (Dasypodidae) (Wenzel 1998). Hence, the common name of “armadillo wasp” is given to some of its representatives. This group is comprised of five described species: S. surinama (Linnaeus, 1767), S. cyanea (Fabricius, 1775), S. chalibea de Saussure, 1852, S. virginea (Fabricius, 1804) and S. septentrionalis Richards, 1978. Phylogenetic studies based on morphological and behavioral (Andena et al. 2009; Cely & Sarmiento 2011; Carpenter et al. 2013) or molecular (Menezes et al. 2015) characters focusing on Synoeca support the monophyly of the genus, but they disagree regarding the relationships among a few of the species.